MANAJEMEN KEGIATAN EKSTRAKURIKULER TERINTEGRASI DENGAN VISI MADRASAH SEBAGAI UPAYA PENGUATAN KURIKULUM DI MI AL IKHLAS PARAKAN KAUMAN TEMANGGUNG JAWA TENGAH - Prada, Yoga Dwi Prada; Dhiniaty Gularso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the management of extracurricular activities integrated with the vision of the madrasah as an effort to strengthen the curriculum at MI Al Ikhlas Parakan Kauman, Temanggung. The problem addressed in this research is the lack of alignment between extracurricular programs and the institutional vision, which may lead to activities that are less effective in supporting student character development and curriculum enhancement. This study aims to describe the planning of extracurricular activities aligned with the madrasah vision, analyze their implementation in supporting curriculum strengthening, and explain the evaluation process conducted to ensure program effectiveness. Using a descriptive qualitative method with a case study design, data were collected through observations, interviews, and documentation involving principals, teachers, students, and parents. The results show that planning is carried out through systematic coordination and needs analysis, ensuring programs align with the madrasah vision. Implementation runs effectively with structured scheduling, active teacher involvement, and integration of religious and character values in each activity. Evaluation is conducted periodically through meetings, monitoring, and reflective assessments, serving as the basis for program improvement. The study concludes that well-managed extracurricular activities integrated with the institutional vision significantly contribute to strengthening the curriculum and developing students’ academic, spiritual, and social competencies.